Football injuries at asian tournaments - Yoon, Y. S.; Chai, M.; Shin, D. W. (The American Journal of Sports Medicine, 2004)
PURPOSE: To examine the incidences and patterns of injuries that required medical attention among Asian football players. METHODS: A total of 411 Asian football players at both senior and youth (U-20) elite levels were observed during 50 international matches. Independent injury observers and team doctors determined the occurrence of injuries and recorded the location, type, time, and circumstances of the injuries using a protocol sheet. RESULTS: The overall injury frequency rate was 45.8 out of 1000 hours. As the tournaments progressed into the knockout stages, the incidence and severity of the injuries increased. The most common sites of injuries were the knees (18.5%), lower legs (17.3%), and ankles (14.2%). Although most injuries were diagnosed as contusions, the more serious injuries were those diagnosed as sprains (especially concerning the knee and ankle) or strains (thigh and back). CONCLUSIONS: The incidences of injuries to Asian football players were higher than those to European players, but the patterns of the injuries showed no major differences. Clinical Relevance: To develop an injury-prevention program, more solid and comprehensive data need to be collected to identify the risk factors and variables associated with higher incidences of injuries to Asian football players.